Do Otolaryngology Patients Show Gender Preference When Choosing a Surgeon? — A Quantitative and Qualitative Analysis - Chitguppi, Chandala; Brar, Tripti (International Archives of Otorhinolaryngology, 2018)
Introduction Otorhinolaryngology has always been considered a gender-neutral specialty, whereas in several other specialties, such as obstetrics, gynecology and urology, gender preference has been consistently shown by patients when choosing their treating surgeon. To date, no study has been performed to analyze whether this practice of gender preference is prevalent in otorhinolaryngology patients too.Objectives To identify if gender preference exists in the field of otorhinolaryngology, specifically in its four subspecialties, namely otology, pediatric otolaryngology, laryngology and head and neck surgery.Methods Patients attending our outpatient department were asked to complete a preformed proforma. The pro forma consisted of two parts, demographic details of the subjects and gender preference in the following subspecialties: otology, pediatric otolaryngology, laryngology and head and neck oncosurgery.Results A total of 1,112 subjects took part in the study, out of which 1,089 subjects were included in the final analysis. Female gender preference was highest in the field of pediatric otolaryngology, while male preference was highest for head and neck oncosurgery.Conclusion Though otorhinolaryngology and head and neck surgery has been considered a gender-neutral field, subspecialties of this field show considerable gender preference.
Keywords: bias; sexism; otolaryngology; male; female